Distribution records of Assamese macaques (Macaca assamensis pelops) from the Bheri River Basin in western Nepal - Khanal, Laxman; Subba, Asmit; Chand, Bijay; Singh, Gobinda Bahadur; Thapa, Bhabilal; Chalise, Mukesh Kumar (Nepalese Journal of Zoology, 2024)
The Assamese macaque (Macaca assamensis) population in Nepal is one of the least studied mammals. It is legally protected by the National Parks and Wildlife Conservation Act 1973; however, its population status, distribution and conservation threats are ill-documented. The species is thought to have a disjunct distribution having limited information about its occurrence in mid-western and far-western Nepal. This study surveyed the Assamese macaques in the Bheri River Basin of western Nepal and recorded their distribution in the basin for the first time. A total of 117 individuals were observed belonging to six different troops with an average troop size of 19.5 individuals. The elevational range of the distribution ranged between 1132 m and 1840 m asl. The Assamese macaque individuals from the Bheri River Basin are much darker and bear longer relative tail lengths than those of eastern and central Nepal. Further explorations and a detailed assessment of conservation threats in western Nepal are warranted.